Connected Spaces and Forcing - Iwasa, Akira (Topology Proceedings, 2022)
We study how forcing destroys connectedness of topological spaces. A topological space is called strongly connected if every continuous real-valued function on it is constant. We give an example where forcing destroys strong connectedness of a space.